Reversible modulation of critical electric fields for a field-induced ferroelectric effect with field-cycling in ZrO2 thin films - Shin, Jonghoon; Shin, Dong Hoon; Kim, Kyung Do; Seo, Haengha; Ye, Kun Hee; Jeon, Jeong Woo; Kim, Tae Kyun; Paik, Heewon; Song, Haewon; Lee, Suk Hyun; Choi, Jung-Hae; Hwang, Cheol Seong (Royal Society of Chemistry, 2024)
This study investigates the effects of field-cycling on the critical electric fields (E-t -> PO and E-PO -> t) of the field-induced ferroelectric (FFE) effect in atomic layer deposited ZrO2 thin films, focusing on their reversibility and temperature dependence. High-field cycling decreases these critical fields, whereas subsequent lower-field cycling effectively rejuvenates them, challenging the previous report of their irreversibility. Elevated temperature experiments reveal that higher temperature increases the lower limit of E-t -> PO reduction, corroborating the thermodynamic predictions of the Landau-Ginzburg-Devonshire (LGD) theory. The rejuvenation effect is also more pronounced at higher temperatures, further corroborating the LGD theory. This study highlights that these reversible transitions between polar and non-polar phases with high- and low-field cycling are a universal phenomenon in fluorite-structured materials, not limited to ferroelectric materials. These findings provide new insights into the field-cycling and temperature-dependent behavior of FFE thin films.